Structure and thermal behavior of zirconium tungstate under heating; IOP Conference Series: Materials Science and Engineering; Vol. 140 : Interdisciplinary Problems in Additive Technologies - Dedova E. S. Elena Sergeevna; Shutilova E. S.; Geber R.; Gomze L. A.; Kulkov S. N. Sergey Nikolaevich (2016, 2016)
Title screen